Alveolar Macrophage Phenotype and Compartmentalization Drive Different Pulmonary Changes in Mouse Strains Exposed to Cigarette Smoke. (3rd July 2020) - De Cunto, Giovanna; Cavarra, Eleonora; Bartalesi, Barbara; Lungarella, Giuseppe; Lucattelli, Monica
Abstract: COPD can manifest itself with different clinical phenotypes characterized by different disease progression and response to therapy. Although a remarkable number of studies have been carried out, little is known about the mechanisms underlying phenotypes that could guide the development of viable future therapies. Several murine strains mirror some human phenotypes after smoke exposure. It was of interest to investigate in these strains whether different pattern of activation of macrophages, and their distribution in lungs, is associated to changes characterizing different phenotypes. We chose C57Bl/6, and Lck deficient mice, which show significant emphysema, DBA/2 mice that develop changes similar to those of "pulmonary fibrosis/emphysema syndrome", p66Shc ko mice that develop bronchiolitis with fibrosis but not emphysema, and finally ICR mice that do not develop changes at 7 months after smoke exposure. Unlike other strains, ICR mice show very few activated macrophages (Mac-3 positive) mostly negative to M1 or M2 markers. On the other hand, a large population of M1 macrophages predominates in the lung periphery of DBA/2, C57Bl/6 and in Lck deficient mice, where emphysema is more evident. M2 macrophages are mainly observed in subpleural and intraparenchymal areas of DBA/2 mice and around bronchioles of p66Shc ko mice where fibrotic changes are present. We observed slight but significant differences in mRNA expression of iNOS, ECF-L, arginase 1, IL-4, IL-13 and TGF-β between air- and smoke-exposed mice. These differences together with the different compartmentalization of macrophages may offer an explanation for the diversity of lesions and their distribution that we observed among the strains.